Генеза та зміст засади публічності в кримінальному процесі - Степанов, О.; Stepanov, О. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Розглянуто основні підходи до розуміння принципу публічності. Проаналізовано його нормативний зміст в умовах змагальної форми кримінального процесу. Подано авторське визначення принципу публічності, у якому відтворено традиційне розуміння цієї засади, а також ураховано норми та принципи Кримінального процесуального кодексу 2012 р.The article considers the basic approaches to understanding of a principle of publicity. The normative content of a principle of publicity in the conditions of the competitive form of criminal procedure is analyzed. Author’s determination of a principle of publicity is made. Courtesy authors’ definition of the principle of publicity, which refers to the principle of criminal procedure, which defines the procedural requirements of purposeful activity and initiative of entities authorized to conduct criminal proceedings designed to protect individuals, society and the state of criminal offenses, protection of rights and legitimate interests of the criminal proceedings and provide quick, full and impartial investigation and trial, so that anyone who has committed a criminal offense, was held liable to the extent of his guilt, no innocent has not been accused or convicted, no one had been subjected to unjustified procedural coercion and that each party to the criminal proceedings was applied due process.
Genesis and Maintenance of Principle of Publicness is in a Criminal Process
Keywords: публічність; кримінальне судочинство; принцип кримінального процесу; засада кримінального процесу; publicity; criminal proceedings; a principle of criminal procedure